2012
DOI: 10.3390/s120202208
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Characterization of Hetero-Core Optical Fiber SPR Sensors Coated with Ta2O5 Film and Their Applications

Abstract: This paper describes the characteristics of optical fiber sensors with surface plasmon resonance (SPR) at 1,310 nm in which the scattering loss of silica optical fiber is low. SPR operation in the infrared wavelength range is achieved by coating a thin tantalum pentaoxide (Ta2O5) film. The novelty of this paper lies in the verification of how the hetero-core scheme could be operated as a commercial base candidate in the sense of easy fabrication, sufficient mechanical strength, and significant sensitivity as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…1(b) illustrates the calculated SPR spectra as functions of wavelength for 25 nm Au / 60 nm Ta2O5 / 5 nm Pd with hydrogen concentrations of 0% and 4%. In this simulation, the reflection coefficient of the multi-layer structure is calculated by the transfer matrix method [13], assuming that there would be a multi-mode distribution [9,10] with the corresponding incident angles in the hetero-core structure. The used dielectric functions of Au, Ta2O5, Pd were taken from the previous literatures [7,14,15].…”
Section: A Spr Hydrogen Tip Sensor Based On Hetero-corementioning
confidence: 99%
See 1 more Smart Citation
“…1(b) illustrates the calculated SPR spectra as functions of wavelength for 25 nm Au / 60 nm Ta2O5 / 5 nm Pd with hydrogen concentrations of 0% and 4%. In this simulation, the reflection coefficient of the multi-layer structure is calculated by the transfer matrix method [13], assuming that there would be a multi-mode distribution [9,10] with the corresponding incident angles in the hetero-core structure. The used dielectric functions of Au, Ta2O5, Pd were taken from the previous literatures [7,14,15].…”
Section: A Spr Hydrogen Tip Sensor Based On Hetero-corementioning
confidence: 99%
“…In addition, our precious experiment showed the excellent reproducibility with a response time (15 s) for 4% hydrogen in the case of 25-nm Au, 60-nm Ta2O5 and 3-nm Pd multi-layer films. The authors have previously reported a variety of hetero-core structured fiber optic SPR sensors [8][9][10] because of the practical advantages in terms of an easy fabrication and the simple structure with no need of cladding removal. The structure consists of a peace of single-mode optical fiber between two multi-mode fibers.…”
Section: Introductionmentioning
confidence: 99%
“…32 To operate the hetero-core optical fiber SPR sensor around 1310 nm, a 60 nm thin layer of tantalum pentaoxide (Ta 2 O 5 ) was deposited over metal layer to sense water using a light emitting diode (LED) and intensity interrogation. 33 The advantage of using 1310 nm wavelength is that the scattering loss of silica optical fiber is low. Using this configuration of the probe a multi-point waterdetection and water-level gauge devise was designed and tested.…”
Section: Fiber Optic Spr Sensor Developmentsmentioning
confidence: 99%
“…In the first type, the light from a broadband source is launched into the fiber through one of the ends and the SPR spectrum of the transmitted light is recorded at the other end, which is the so-called transmission-based setup. [15][16][17] In the transmission-based setup, the authors have proposed a preliminary version of a differential SPR-based sensor specifically designed for permanent monitoring, mainly in the areas of environment and safety. 18,19 The unwanted impacts in long-term monitoring are perturbations from the mechanical setup or drifts in the electronic circuits or misalignment between source/detector and coated optical fiber.…”
Section: Introductionmentioning
confidence: 99%